Аналіз результатів факоемульсифікації катаракти ускладненої сублюксацією кришталика - Завгородня, Наталія Григорівна; Саржевський, Андрій Сергійович; Zavgorodnjaja, N. G.; Sarzhevsky, A. S. (My University, 2013)
In this article we present our experience with the modified method implant CTR in patients with severe lens subluxations of the different origin. The purpose is to assess the efficacy of this method. 84 patients (86 eyes) with a cataract at the age of 51-86 years (mean age 69,8±9,6) including, 46 women and 38 men were examined. These results confirm the relatively high efficiency of the proposed method of implantation of capsular tension ring in cataract surgery for the patients with zonular weakness.
Analysis of the results of cataract phacoemulsification complicated by lens subluxations
Keywords: факоемульсифікація катаракти; сублюксація кришталика; капсульне кільце